2017
DOI: 10.1158/1078-0432.ccr-16-1922
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Clinical Relevance of Associated Genomic Alterations in MYD88 L265P and non-L265P–Mutated Diffuse Large B-Cell Lymphoma: Analysis of 361 Cases

Abstract: mutations, notably the recurrent gain-of-function L265P variant, are a distinguishing feature of activated B-cell like (ABC) diffuse large B-cell lymphoma (DLBCL), leading to constitutive NFκB pathway activation. The aim of this study was to examine the distinct genomic profiles of -mutant DLBCL, notably according to the presence of the L265P or other non-L265P MYD88 variants. A cohort of 361 DLBCL cases (94 mutant and 267 wild-type) was submitted to next-generation sequencing (NGS) focusing on 34 genes to ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 50 publications
(63 reference statements)
6
108
1
Order By: Relevance
“…Somatic variant calling was performed by VarScan, using germline DNA as a reference. Variant annotation was performed by GenerateReports software, as previously described . To confirm some genetic variants, BL1 and BL2 tumor DNA was also analyzed using our in‐house dedicated lymphopanel, as previously reported …”
Section: Methodsmentioning
confidence: 99%
“…Somatic variant calling was performed by VarScan, using germline DNA as a reference. Variant annotation was performed by GenerateReports software, as previously described . To confirm some genetic variants, BL1 and BL2 tumor DNA was also analyzed using our in‐house dedicated lymphopanel, as previously reported …”
Section: Methodsmentioning
confidence: 99%
“…Given the critical role of BCR/PI3K signaling in the pathogenesis of germinal center-derived lymphomas 8 such as Burkitt lymphoma (BL) and diffuse large B-cell lymphomas (DLBCL), 9,10 the occurrence of FOXO1 mutations in these malignancies is of great interest. FOXO1 mutations have been identified in up to 11% of adult DLBCL, [11][12][13][14][15][16][17][18] and FOXO1 has been identified as a driver gene in DLBCL cell lines. 15 DLBCL with mutations of the M1 residue, resulting in loss of the AKT recognition motif, or within this motif itself, have aberrant nuclear localization of FOXO1 and are associated with a poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…On behalf of the Lymphoma Study Association group, we previously reported the genetic context of 94 MYD88mutated DLBCL patients. 1 This study further highlighted the strong association of the L265P variant with the activated B-cell like (ABC) signature, compared with the non-L265P mutations that distribute between the different DLBCL subtypes. We also observed frequent additional genetic abnormalities involving the NF-kB/Bruton tyrosine kinase pathway in these cases, including CARD11, TNFAIP3, or CD79B alterations, indicating that this mutation needs to be interpreted in a global genetic background.…”
mentioning
confidence: 74%